2020
DOI: 10.31557/apjcp.2020.21.3.663
|View full text |Cite
|
Sign up to set email alerts
|

Arg399Gln XRCC1 Polymorphism and Risk of Squamous Cell Carcinoma of the Head and Neck in Jordanian Patients

Abstract: 1999). X-ray repair cross-complementing group 1 (XRCC1) is a key protein in BER and closely associated with BER pathway coordination due to interacting with most components of the BER short-patch pathway (Caldecott et al., 1996; Marintchev et al., 2000). There are many single

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…XRCC1 is essential in the assembly of the BER pathway because it interacts and coordinates other major components such as polyADP-ribose polymerase-1 enzyme, DNA polymerase H, and DNA ligase III, which are all involved in the repair of single-stranded DNA breaks induced by ROS (Fig. 1B) [11][12][20][21][22]. The XRCC1 gene is located on chromosome 19q13.2 with a length of 33 kb, and comprises 17 exons and 16 introns [12,14,19].…”
Section: State Of Knowledgementioning
confidence: 99%
See 2 more Smart Citations
“…XRCC1 is essential in the assembly of the BER pathway because it interacts and coordinates other major components such as polyADP-ribose polymerase-1 enzyme, DNA polymerase H, and DNA ligase III, which are all involved in the repair of single-stranded DNA breaks induced by ROS (Fig. 1B) [11][12][20][21][22]. The XRCC1 gene is located on chromosome 19q13.2 with a length of 33 kb, and comprises 17 exons and 16 introns [12,14,19].…”
Section: State Of Knowledgementioning
confidence: 99%
“…Some polymorphisms in the XRCC1 gene have been used as biomarkers of susceptibility to DNA damage by pesticides. In this regard, the clinically relevant polymorphisms are rs1799782 (exon 6 Arg194Trp C/T) and rs25487 (exon 10 Arg399Gln G/A) [12][13][19][20][21]. The Arg194Trp polymorphism is located between two protein domains: the NH2-terminal domain and the BRCT1 domain that directly affects enzymatic function [14,19].…”
Section: State Of Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…DNA repair systems are key to maintain genomic integrity and play crucial roles in preventing mutations. X-ray Repair cross complementing Group 1 (XRCC1) is a common DNA repair gene that mainly engages in DNA base excision repair (BER), nucleotide excision repair (NER) and chain fracture repair, 5 Studies have shown that single nucleotide polymorphisms (SNP) in the coding region or population can affect DNA repair ability and is closely related to genetic susceptibility of many tumors including HNC. 5 The most common SNPs leading to amino acid substitution are at exons 6 (Arg194Trp) and 9 (Arg280His) and 10 (Arg399Gln).…”
Section: Introductionmentioning
confidence: 99%
“…X-ray Repair cross complementing Group 1 (XRCC1) is a common DNA repair gene that mainly engages in DNA base excision repair (BER), nucleotide excision repair (NER) and chain fracture repair, 5 Studies have shown that single nucleotide polymorphisms (SNP) in the coding region or population can affect DNA repair ability and is closely related to genetic susceptibility of many tumors including HNC. 5 The most common SNPs leading to amino acid substitution are at exons 6 (Arg194Trp) and 9 (Arg280His) and 10 (Arg399Gln). Interestingly, these amino acid changes may affect protein-protein interactions between XRCC1 and other BER proteins, which in turn may alter DNA repair capabilities.…”
Section: Introductionmentioning
confidence: 99%